Evaluasi Pembelajaran Membaca di Kelas Tinggi - Fadillah Annisa; Hilda Melani Purba; Nurhafizah Nurhafizah; Juni Sahla Nasution (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
Evaluation of reading learning in higher grades is a process to find out how many students are able to understand information, receive information, categorize, analyze and conclude information, accuracy of pronunciation and intonation when reading language texts. This research aims to determine the purpose of evaluating reading learning and the types of evaluation of reading learning in higher grades. The research method used is a qualitative research method with literature study. The research results show that the evaluation of reading learning aims to gain knowledge (information), foster the development of compassion and beauty, and fill free time. The types of evaluation of reading learning in higher grades are diagnostic evaluation, selective evaluation, formative evaluation, and summative evaluation.